Intravitreal Ranibizumab or Aflibercept After Bevacizumab in Diabetic Macular Edema: Exploratory Retrospective Analysis - Pessoa, Bernardete (2021)
Aim: To evaluate the efﬁcacy of switching from bevacizumab to ranibizumab or aflibercept in eyes with diabetic macular edema (DME) unresponsive to bevacizumab. Methods: Single-center retrospective comparative study of patients with DME unresponsive to intravitreal bevacizumab that was switched to ranibizumab or aflibercept. Best-corrected visual acuity (BCVA) and central foveal thickness (CFT) were analysed prior to and 4 months after the switch. Ocular coherence tomography (OCT) biomarkers were also analysed. Results: Fifty-six eyes from 40 patients were included in the study, 33 eyes switched to ranibizumab and 23 to aflibercept. A significant median CFT decrease was observed in both groups (p<0.001), with no between-group differences. BCVA gain was only significant in the ranibizumab group (p<0.001). None of the pre-baseline or baseline parameters were associated with the response to ranibizumab or aflibercept. Conclusion: In persistent DME unresponsive to bevacizumab, both anatomical and functional improvements were observed with ranibizumab whereas aflibercept only showed an anatomical improvement. Clinicaltrials.gov NCT04018833.